Hubungan Stres Kerja Dengan Kecelakaan Kerja Pada Pekerja Di Bagian Pemanen Kelapa Sawit Di PT.X di Desa Gale-Gale Kabupaten Maluku Tenggah Provinsi Maluku - Zulfikar Lating; Ira Deseilla Pawa; Iswandi Fataruba (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Work stress is one of the main concerns for occupational safety and health for workers, both in the field of welfare and health. It has been estimated that about half of all workers absenteeism and work accidents at work are caused by disorders related to work-related stress. This study aims to determine the relationship between work stress and work accidents on workers in the oil palm harvesting section. This research is an analytic observational research which is directed to explain a situation or situation, using a cross sectional approach. The results of this study show that there is a positive relationship between work stress and the risk of work accidents. The results of statistical analysis using the Chi-Square test obtained a p-value of 0.005 when compared to the degree of significance (p-value <0.05). Suggestions for the company can be used as reference material for training K3 workers in the company to increase awareness of occupational health and safety in the company.